MICROSCALE STRUCTURAL ASPECTS OF VEGETATION DENSITY VARIABILITY - Cosh M.H.; Brutsaert W. (My University, 2003)
Current radiometric remote sensing technology enables high resolution data of vegetation biomass to be obtained in the form of the Normalized Difference Vegetation Index (NDVI). The present study uses such data to examine the spatial structure of vegetation density at the land surface by wavelet, semivariogram, and spectral analyses. Within the range of 30-800m, the results show that vegetation density of arable cropland is persistent and can be characterized as a fractal with a dimension of 1.59. Within the same range of distances, vegetation density across a more diverse landscape (including besides cropland, also pasture and savanna) exhibits a fractal dimension of 1.69. In the Southern Great Plains, this range is of the order of the typical size of agricultural fields.
Keywords: VEGETATION; FRACTAL DIMENSION; SPECTRAL ANALYSIS; VARIOGRAM; VARIABILITY